Survey of cache technology for VoiceXML-based voice platform - WANG Wen-lin; LIAO Jian-xin; ZHU Xiao-min (Tongxin xuebao)
The basic elements and perfect attributes of cache system in VoiceXML-based voice platform were presented,and the difference between WWW environment and VoiceXML-based voice platform was introduced.The cache content selection,cache replacement algorithm,cache consistency control algorithm and content prefetch and theirs applications in VoiceXML-based voice platform were analyzed.Finally,the further researches of cache technology in VoiceXML-based voice platform are addressed.